THE STRUCTURE OF LANDSCAPES AND THEIR TRANSFORMATION UNDER THE INFLUENCE OF MODERN ANTHROPOGENIC PROCESSES (Scientific journal of the Fergana State University, 2023)
This article provides information that currently the nature of the world and our country is changing as a result of anthropogenic influences, as a result of these changes, various changes are observed in all landscape complexes of nature, as well as natural-anthropogenic landscape complexes as a result of the development of new lands, as well as environmental problems such as desertification, salinity, degradationMeasures to eliminate these environmental problems are also outlined.